\[\boxed{\text{133\ (133).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ 2x - 12 = 2 \cdot (x - 6)\]
\[2x - 12 = 2x - 12\]
\[тождество.\]
\[2)\ a - b = - (b - a)\]
\[a - b = - b + a\]
\[a - b = a - b\]
\[тождество.\]
\[3)\ 3m + 9 = 3 \cdot (m + 9)\]
\[3m + 9 = 3m + 27\]
\[не\ тождество.\]
\[4)\ (a + b) \cdot 1 = a + b\]
\[a + b = a + b\]
\[тождество.\]
\[5)\ (a + b) \cdot 0 = a + b\]
\[0 = a + b\]
\[не\ тождество.\]
\[6)\ (a - a) \cdot (b + b) = 0\]
\[0 \cdot 2b = 0\]
\[0 = 0\]
\[тождество.\]
\[7)\ 3a - a = 3\]
\[2a = 3\]
\[не\ тождество.\]
\[8)\ 4x + 3x = 7x\]
\[7x = 7x\]
\[тождество.\]
\[9)\ a - (b + c) = a - b + c\]
\[a - b - c = a - b + c\]
\[не\ тождество.\]
\[10)\ m + (n - k) = m + n - k\]
\[m + n - k = m + n - k\]
\[тождество.\]
\[11)\ 4a - (3a - 5) = a + 5\]
\[4a - 3a + 5 = a + 5\]
\[a + 5 = a + 5\]
\[тождество.\]
\[12)\ (a - 5) \cdot (a + 3) =\]
\[= (5 - a) \cdot (3 + a)\]
\[(a - 5) \cdot (a + 3) =\]
\[= - (a - 5) \cdot (a + 3)\]
\[не\ тождество.\ \]
\[\boxed{\text{133.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ (4x + 1) - (7x + 2) = x\]
\[4x + 1 - 7x - 2 - x = 0\]
\[- 4x = 1\]
\[12x - 9 = c + 5\]
\[12 \cdot \left( - \frac{1}{4} \right) - 9 = c + 5\]
\[- 3 - 9 = c + 5\]
\[- 12 - 5 = c\]
\[c = - 17\]
\[Ответ:\ c = - 17.\]
\[2)\ 6 - 3 \cdot (2x - 4) = - 8x + 4\]
\[6 - 6x + 12 = - 8x + 4\]
\[- 6x + 8x = 4 - 6 - 12\]
\[2x = - 14\]
\[\frac{1}{7}cx = x + c\]
\[\frac{1}{7} \cdot ( - 7) \cdot c = - 7 + c\]
\[- c - c = - 7\]
\[- 2c = - 7\]
\[c = \frac{7}{2}\]
\[c = 3,5\]
\[Ответ:c = 3,5.\]